Renewables projects in peripheries: determinants, challenges and perspectives of biogas plants – insights from Central European countries. Issue 1 (1st January 2020) - Chodkowska-Miszczuk, Justyna; Martinat, Stanislav; Kulla, Marián; Novotný, Ladislav
ABSTRACT: Biogas energy has been introduced into Central and Eastern European countries (CEECs) through various incentives after their accession to the European Union in 2004. This paper contributes to an understanding of the determinants, challenges and perspectives of agricultural biogas plants in three CEECs (Poland, Slovakia, Czech Republic). Using a combination of quantitative (surveys) and qualitative (semi-structured interviews) methods, it particularly addresses varieties in public support for biogas sectors, how the relationships between biogas plants as new energy entities and their locations in rural peripheries are constructed, and how the operation of biogas plants influences local rural development. We found that as a result of various agriculture and agricultural policies in Poland, Slovakia and the Czech Republic in the second half of the 20th century, the preconditions for the incorporation of agricultural biogas plants into agriculture and rural space generally differ significantly. While in the Czech Republic and Slovakia agricultural biogas plants were usually established within large-scale agricultural farms, in Poland these are rather located off-farm. The most profound challenge for today's biogas plants in all the CEECs studied lies in the transition from direct public incentives to a more self-sufficient business-oriented model focused on cooperation, participation and the involvement of local stakeholders in decision-making, as well as the energy utilization of locally generated agricultural waste and biowaste from households. By accommodation of these principles, agricultural biogas plants in CEECs might become a more useful and sustainable element of the rural energy transition.